Implementasi Etnomatematika Pada Bangunan Kuno Kawasan Kampung Kemasan Gresik Dengan Menggunakan Metode Kooperatif Tipe Group Investigation (GI) Untuk Meningkatkan Komunikasi Siswa Pada Materi Bangun Ruang - Aulia, Nurul Rakhma; Wahyuni, Indah (Program Studi Sarjana Pendidikan Matematika, Universitas Singaperbangsa Karawang, 2024)
The purpose of this research is to improve students' mathematical communication using the Cooperative Group Investigation (GI) learning method. The instruments used in the research were assessment questionnaire sheets and questionnaire sheets in the form of Student Worksheets (LKPD) given by the teacher to students. the results obtained, including: a. Mathematical communication skills between students can be increased b. students can understand the material build space.